2014
DOI: 10.4028/www.scientific.net/kem.631.30
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Synthesis and Characterization of SiO<sub>2</sub>-CaO-P<sub>2</sub>O<sub>5</sub>-SrO Bioactive Glass: <i>In Vitro</i> Study

Abstract: Bioactive glass of the type CaO–SrO–P2O5–SiO2was obtained by the sol-gel processing method. Three samples containing 0 mol%, 5 mol% and 10 mol% of SrO were synthesized. The obtained bioactive glasses were characterized by the techniques such as, X-ray diffraction (XRD) and scanning electron microscope (SEM) and the effect of SrO/CaO substitution on in vitro biological properties of the synthesized glasses were evaluated and biocompatibility of the samples was measured using MTT assay. The results showed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…4,5 Fillers have been traditionally obtained by grinding minerals such as quartz, glasses, barium glass, silica, zirconium oxide or sol-gel-derived ceramics. 57 Dental composites are classified according to their filler particle size to macro-filled composites; micro-filled composites and hybrid composites. Among of these classifications, the hybrid composite is beneficial, as it contains a good distribution of filler in different sizes.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Fillers have been traditionally obtained by grinding minerals such as quartz, glasses, barium glass, silica, zirconium oxide or sol-gel-derived ceramics. 57 Dental composites are classified according to their filler particle size to macro-filled composites; micro-filled composites and hybrid composites. Among of these classifications, the hybrid composite is beneficial, as it contains a good distribution of filler in different sizes.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 50 egg shells were not detected after one month of implantation in laboratory animals [5,9,10]. In recent study, some bioactive glass such as CaO-SrO-P2O5-SiO2 was obtained by the sol-gel processing method, evaluated by X-ray diffraction technique, the results showed that they are non-toxic and revealed good biocompatibility [27]. After three months of treatment, no encapsulation, inflammation was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the solegel process, it is possible to fabricate ceramic or glass materials in a wide variety of forms, including ultrafine or spherical shaped powders, thin film coatings, ceramic fibers, microporous inorganic membranes, monolithic ceramics and glasses, or extremely porous aerogel materials [46]. Applying the solegel process, it is possible to fabricate ceramic or glass materials in a wide variety of forms, including ultrafine or spherical shaped powders, thin film coatings, ceramic fibers, microporous inorganic membranes, monolithic ceramics and glasses, or extremely porous aerogel materials [46].…”
Section: Gelationmentioning
confidence: 99%